Electroconvulsive therapy suppresses the neurotoxic branch of the kynurenine pathway in treatment-resistant depressed patients. Issue 1 (December 2016) - Schwieler, Lilly; Samuelsson, Martin; Frye, Mark; Bhat, Maria; Schuppe-Koistinen, Ina; Jungholm, Oscar; Johansson, Anette; Landén, Mikael; Sellgren, Carl; Erhardt, Sophie
Abstract Background Neuroinflammation is increasingly recognized as contributing to the pathogenesis of depression. Key inflammatory markers as well as kynurenic acid (KYNA) and quinolinic acid (QUIN), both tryptophan metabolites, have been associated with depressive symptoms and suicidality. The aim of the present study is to investigate the peripheral concentration of cytokines and tryptophan and kynurenine metabolites in patients with unipolar treatment-resistant depression before and after electroconvulsive therapy (ECT), the most effective treatment for depression. Methods Cytokines in plasma from patients with major depressive disorder (MDD;n  = 19) and healthy volunteers (n  = 14) were analyzed with electrochemiluminescence detection. Tryptophan and kynurenine metabolites were detected with high-performance liquid chromatography (HPLC) and LC/MS. KYNA was analyzed in a second healthy control cohort (n  = 22). Results Patients with MDD had increased plasma levels of interleukin (IL)-6 compared to healthy volunteers (P  < 0.05). We also found an altered kynurenine metabolism in these patients displayed by decreased plasma levels of KYNA (P  < 0.0001) as well as a significantly increased QUIN/KYNA ratio (P  < 0.001). Plasma levels of tryptophan, kynurenine, and QUIN did not differ between patients and controls. Treatment with ECT was associated with a significant decrease in the plasma levels of tryptophan (P  < 0.05), kynurenine (P  < 0.01), and QUIN (P  < 0.001), whereas plasma levels of KYNA did not change. The QUIN/KYNA ratio was found to significantly decrease in ECT-treated patients (P  < 0.05). There was a significant inverse correlation between symptom severity and kynurenine levels at baseline (r  = −0.67, P  = 0.002). Conclusions This study confirms an imbalanced kynurenine pathway in MDD supporting the hypothesis of a netstimulation ofN -methyl-d -aspartic acid (NMDA) receptors in the disorder. Treatment with ECT profoundly decreased QUIN, an NMDA-receptor agonist previously suggested to be implicated in the pathogenesis of depression, an effect that might have bearing for the good clinical outcome of ECT.